Local community perception of Batik Parijotho Salak as a cultural identity of Sleman - Kurniawan, Wahyu (Privietlab, 2025)
Salak Parijotho: A sign of the cultural identity of Sleman Regency, Special Region of Yogyakarta, batik is an expression of creativity. The goal of this research was to examine and assess how local residents view Parijotho Salak Batik as Sleman's cultural identity. This study employed a descriptive qualitative method of data collection, which included thorough interviews, participatory observations, and documentation. The younger generation views it as a potentially creative economy that can be developed, while artists and cultural icons see it as a cultural legacy that must be protected. The salak motif, which is typical of this batik, symbolizes Sleman's distinctiveness as the top producer of salak. Additionally, the research revealed obstacles to conservation and growth, such as inadequate promotion, competition with contemporary textile goods, and a scarcity of skilled artisans. The study's conclusion indicates that, while Parijotho Salak Batik has potential as a solid cultural identity, cooperation between the government, creative industry participants, and the community is necessary to maintain and foster it. In the context of modernization and globalization, these results add to a thorough understanding of the dynamics of local cultural identity.